Determination of Methamphetamine by High-Performance Liquid Chromatography in Odor-Adsorbent Material Used for Training Drug-Detection Animals - Ning Sun; Jingjing Chao; Xiaochang Liu; Hao Li; Dongshun Jia; Dajun Zhang; Liuwei Xie; Yuanting Zhou; Wenxuan Lang; Yingyi Shui; Qiwen Zhu (Molecules, 2024)
The objective of the present report was to develop and validate a simple, sensitive, and selective analytical method for the determination of methamphetamine in an odor-adsorbent material (gauze) which was used to improve and standardize the training method used for drug-detection animals. High-performance liquid chromatography (HPLC) was performed using a Spherisorb ODS2 C18 column (200 mm × 4.6 mm, 5 μm), with a mobile phase consisting of a 0.25% methanol/triethylamine aqueous solution (V:V = 20:80), the pH of which was adjusted to 3.1 using glacial acetic acid, at a flow rate of 1.0 mL/min. The column temperature was 25 °C, and the detection of the analytes was performed at a wavelength of 260 nm. Methamphetamine showed good linearity (R2 = 0.9999) in the range of 4.2~83.2 mg/mL. The stability of the test material was good over 24 h. The precision of the method was good, with an average spiked recovery of 86.2% and an RSD of 2.9%. The methamphetamine content in the gauze sample was determined to be 7.8 ± 2.2 μg/sample. A high-performance liquid chromatography (HPLC) method was optimized and validated for the determination of methamphetamine in adsorbent materials (gauze). Validation data in terms of specificity, linearity, the limit of detection and the limit of quantification, reproducibility, precision, stability, and recovery indicated that the method is suitable for the routine analysis of methamphetamine in adsorbent materials (gauze) and provided a basis for training drug-detection animals.